A Prospective, Randomized Comparison of Clinical Outcomes with Different Processing Techniques in Autologous Fat Grafting. Issue 5 (22nd August 2022) - Hanson, Summer E.; Garvey, Patrick B.; Chang, Edward I.; Reece, Gregory P.; Liu, Jun; Baumann, Donald P.; Butler, Charles E.
Abstract : Background: Autologous fat grafting is a useful tool in breast reconstruction. The authors have previously demonstrated a difference in the rate of processing adipose grafts in a randomized time and motion clinical trial. The purpose of this study was to compare clinical outcomes in commonly used grafting systems. Methods: Three methods to prepare adipose grafts were compared: a passive washing filtration system (Puregraft system), an active washing filtration system (Revolve system), and centrifugation (Coleman technique). Postoperative complications, rates of fat necrosis, revision procedures, and additional imaging were recorded. Results: Forty-six patients were included in the prospective, randomized study (15 active filtration, 15 passive filtration, and 16 centrifugation). Their mean age was 54 years and mean body mass index was 28.6 kg/m 2 . The mean length of follow-up was 16.9 ± 4 months. The overall complication rate was 12.1 percent. The probability of fat necrosis was no different between the groups (active filtration, 15 percent versus passive filtration, 14.3 percent] versus centrifugation, 8 percent; p = 0.72). Fat necrosis was highest in patients with breast conservation before grafting (60 percent; p = 0.011). There was no significant difference in contour irregularity (active filtration, 40 percent versus passive filtration, 38 percent versus centrifugation, 36 percent; p = 0.96) or additional grafting (active filtration, 40 percent versus passive filtration, 24 percent versus centrifugation, 32 percent; p = 0.34). Conclusions: This is the first prospective, randomized study to compare clinical outcomes of adipose graft preparation. There was no significant difference in early complications, fat necrosis, or rates of additional grafting among the study groups. There was significantly higher risk of fat necrosis in patients with previous breast conservation treatment regardless of processing technique. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, II.